2018
DOI: 10.6007/ijarbss/v8-i4/4150
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Sensory Balls in the Classroom: Effects on Behavioural and Academic Functioning of Students with Learning Disabilities

Abstract: The purpose of this study is to investigate class-wide effects using an A-B-A-B reversal design, examining the effectiveness of sensory balls in comparison to classroom chairs in a special education classroom. Students' on-task and out-of-seat behaviour were measured using behaviour observation ratings. The writing productivity were measured using Kurikulum Standard Sekolah Rendah Pendidikan Khas. Participants in the study consist of eight students with learning disabilities (ADHD and ASD). During baseline, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Since 1991, there has been an increasing information about the benefits of using balls as an adaptive seating to replace chairs in schools of Europe. It was found that active seating has many benefits in preventing back injury, improving poor hand writing, helping hyperactive children to be calmer, and focusing for longer time as well as helping other children to concentrate better with better understanding of subject materials [7]. Therapy balls as an alternative seating device help to facilitate positive classroom behaviors, mental health, and fitness [8].…”
Section: Introductionmentioning
confidence: 99%
“…Since 1991, there has been an increasing information about the benefits of using balls as an adaptive seating to replace chairs in schools of Europe. It was found that active seating has many benefits in preventing back injury, improving poor hand writing, helping hyperactive children to be calmer, and focusing for longer time as well as helping other children to concentrate better with better understanding of subject materials [7]. Therapy balls as an alternative seating device help to facilitate positive classroom behaviors, mental health, and fitness [8].…”
Section: Introductionmentioning
confidence: 99%